2021
DOI: 10.1371/journal.pone.0249547
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Candida albicans in dual-species biofilms with antifungal treatment reduces Staphylococcus aureus and MRSA in vitro

Abstract: Polymicrobial biofilms consisting of fungi and bacteria are frequently formed on endotracheal tubes and may contribute to development of ventilator associated pneumonia (VAP) in critically ill patients. This study aimed to determine the role of early Candida albicans biofilms in supporting dual-species (dual-kingdom) biofilm formation with respiratory pathogens in vitro, and investigated the effect of targeted antifungal treatment on bacterial cells within the biofilms. Dual-species biofilm formation between C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…tropicalis and C. tropicalis–S. marcescens 52 , Staphylococcus xylosus – S. aureus 53 etc. It was observed that ocular isolates of C. albicans, S. aureus and S. epidermidis formed polymicrobial mixed biofilms irrespective of whether the bacteria and fungus were added simultaneously onto the substratum, or the bacterium was added to the preformed fungal biofilm or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…tropicalis and C. tropicalis–S. marcescens 52 , Staphylococcus xylosus – S. aureus 53 etc. It was observed that ocular isolates of C. albicans, S. aureus and S. epidermidis formed polymicrobial mixed biofilms irrespective of whether the bacteria and fungus were added simultaneously onto the substratum, or the bacterium was added to the preformed fungal biofilm or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism by which anidulafungin reduces PNAG production remains to be determined, the authors suggest that it may inhibit activity of PNAG synthesis protein IcaA ( 79 ). However, the anidulafungin-mediated reduction of C. albicans biofilm growth may also contribute to enhanced killing of S. aureus in biofilm, as reducing C. albicans burdens in a polymicrobial biofilm consequently reduces the protective effect of C. albicans on S. aureus antibiotic resistance ( 56 , 80 ). One proposed mechanism of reduced antibiotic efficacy towards S. aureus in a C. albicans biofilm relative to a mono-microbial biofilm is through a physical barrier of the biofilm preventing appropriate diffusion of the antibiotics.…”
Section: Albicans-s Aureus Biofilm Interactionsmentioning
confidence: 99%
“…Due to the previous reports on facilitation of bacterial biofilms by Candida spp. (Rodrigues et al, 2019;Phuengmaung et al, 2020;Luo et al, 2021), expression of several genes of S. epidermidis biofilms production was explored (Figures 4A-I). The synthesis pathway for PIA, a polymer of uridine diphosphate N-acetylglucosamine (UDP-Glc-NAc) of S. epidermidis ECM, and the possible association with Candida, is demonstrated in Figure 4I.…”
Section: Staphylococcus Epidermidis Biofilms Possibly Through the Downregulation And Upregulation Of Genes For Biofilm Suppression And Admentioning
confidence: 99%